2022
DOI: 10.1371/journal.pone.0269806
|View full text |Cite|
|
Sign up to set email alerts
|

Trace element concentrations in forage seagrass species of Chelonia mydas along the Great Barrier Reef

Abstract: Toxic metal exposure is a threat to green sea turtles (Chelonia mydas) inhabiting and foraging in coastal seagrass meadows and are of particular concern in local bays of the Great Barrier Reef (GBR), as numerous sources of metal contaminants are located within the region. Seagrass species tend to bioaccumulate metals at concentrations greater than that detected in the surrounding environment. Little is known regarding ecotoxicological impacts of environmental metal loads on seagrass or Chelonia mydas (C. mydas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…Cobalt was consistently higher not only in coastal C. mydas populations but particularly in Upstart Bay turtles. Such findings are true not only for the blood and scute analyses conducted in the present study but also in previous analyses of C. mydas blood (Villa et al, 2017), scutes (Villa et al, 2019), and seagrass species within the same study region (Thomas et al, 2020; Wilkinson et al, 2022). Concentrations of Co reported in Upstart Bay are purportedly the highest reported in blood collected from marine turtles or other vertebrates from anywhere else in the world (Villa et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Cobalt was consistently higher not only in coastal C. mydas populations but particularly in Upstart Bay turtles. Such findings are true not only for the blood and scute analyses conducted in the present study but also in previous analyses of C. mydas blood (Villa et al, 2017), scutes (Villa et al, 2019), and seagrass species within the same study region (Thomas et al, 2020; Wilkinson et al, 2022). Concentrations of Co reported in Upstart Bay are purportedly the highest reported in blood collected from marine turtles or other vertebrates from anywhere else in the world (Villa et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…It was predicted that C. mydas blood metal concentrations would be lower at the control site (Howick Island Group) compared with each coastal site studied. Previous research in this region showed that metal concentrations were consistently higher in coastal C. mydas blood (Villa et al, 2017) and forage material (seagrass; Thomas et al, 2020; Wilkinson et al, 2022) compared with the natural baseline metal levels in an area minimally influenced by land‐based contaminants and industrial activity, Howick Island Group (Villa et al, 2017). In the present study, several elements (Al, Co, Mg, and Mn) were occasionally higher in blood collected from one or more coastal sites compared with the Howick Island Group, though most elements were detected at similar concentrations between sites.…”
Section: Discussionmentioning
confidence: 92%
“…K. Mishra & Farooq, 2022a;Nikalje & Suprasanna, 2018;Rainbow, 2007). Once trace metals are accumulated in seagrass tissues, they are transferred to seagrass associated herbivores (e.g., fish and turtles), detritus grazers, leaf epiphytes and other organisms and gets biomagnified in trophic food chains and webs (Jiang et al, 2023;Schneider et al, 2018a;Suheryanto & Ismarti, 2018;Wilkinson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves can also uptake and translocate these pollutants within their tissues, leading to their bioaccumulation (Analuddin et al, 2017;Arumugam et al, 2018;Dudani et al, 2017). Moreover, seagrasses have the capacity to absorb heavy metals and can be used for phytoremediation in polluted water bodies, although their exposure to these substances severely impacts their health (Yadav et al, 2021), and that of grazers by bioaccumulation (Wilkinson et al, 2022).…”
Section: Chemical Pollutionmentioning
confidence: 99%